Understanding the freezing of biopharmaceuticals: First‐principle modeling of the process and evaluation of its effect on product quality. Issue 8 (17th June 2013) - Radmanovic, Nikola; Serno, Tim; Joerg, Susanne; Germershaus, Oliver
Abstract: Freezing and thawing are important process steps in the manufacture of numerous biopharmaceuticals. It is well established that these process steps can significantly influence product quality attributes (PQA). Herein, we describe a physico‐mathematical model to predict product temperature profiles based on the freezing program as input parameter in a commercial freeze–thaw module. Applying this model, the time from first nucleation until the last point to freeze (LPF) reaching −5°C and the time from −5°C at LPF to −30°C at LPF was varied to study the effect on PQA in a full factorial design. Effects of process parameter settings on a typical fully formulated, highly concentrated monoclonal antibody (mAb) solution as well as highly concentrated mAb solution formulated with buffer only were investigated. We found that both process phases affected PQA, such as aggregates by size‐exclusion chromatography, polydispersity index by dynamic light scattering, and number of subvisible particles and turbidity in a complex way. In general, intermediate cooling and freezing times resulted in overall optimized PQA. Fully formulated mAb solution containing cryoprotectant and nonionic surfactant was significantly less affected by freezing–thawing than mAb solution formulated in buffer only. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2495–2507, 2013